Developing E-Book Contained Character Values in PPKn Lesson Content Grade V Elementary School - Filivani, Putu Nita; Agung, Anak Agung Gede (Journal of Education Technology, 2021)
Teachers are not innovated in developing media, therefore students’ interaction in online learning was not optimal. This issue raised a new problem such as, lack of deepening character values for students. The media developed was an E-Book containing character values. Therefore, this research aims to describe the design process of E-Book product with character values and find out the results of E-Book validation according to the results of expert reviews, individual try-outs, and small group try-outs. The type of this research was a development research by applying ADDIE model (analyze, design, development, implementation, evaluation). Then, data collection method which used was questionnaire and quantitative descriptive analysis method. The results of data analysis were gained based on media validation assessed by content learning experts obtained a score of 91,67% with very good qualifications, instructional design expert obtained a score of 100% with very good qualifications, learning media expert obtained a score of 95,00% with very good qualifications. The results of individual user test on 3 students obtained a score of 95,83% with very good qualifications, and the user test through small group test on 12 student obtained a score of  97,50% with very good qualifications. Based on the results of the product test data analysis by experts (content learning expert, instructional design expert, learning media expert) and user subject test results (students), it can be concluded that E-Book media containing character values were suitable to be used in PPKn learning subject for 5th grade elementary school students. The implication of using E-Book as technology-based learning media supported by existing facilities and infrastructure in schools such as internet access (WiFi), computers / laptops, LCDs, projectors, as well as the readiness and skills of teachers and students in accessing E-Book media.